Rancangan Aplikasi Monitoring Maintenance Mesin Mini ATM - Dian Cahyadi; Timur Dali Purwanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Monitoring maintenance of mini ATM machines at PT Bank Mandiri (Persero) Tbk Palembang Sudirman Area currently uses the minutes of handing over of Mini ATM machines which are recorded in Microsoft Excel, this could be the reason monitoring of maintenance for mini ATM machines has not gone well, such as in the case of officers having difficulty monitoring the progress of repairing Mini ATM machines, then from the agent's point of view complaints cannot always be responded to quickly, so the SLA for repairing Mini ATM machines has not been fulfilled. Based on these things the author wants to build a web-based application using the waterfall method, starting with data collection through observation and interviews, analysis of system requirements, design, code, testing, support, the hope is that this monitoring application is made so that all parties related to the maintenance process will get convenience in the process of monitoring customer complaints and fulfilling the Mini ATM Machine maintenance SLA